Correction: A 2-formylphenylboronic acid (2FPBA)-maleimide crosslinker: a versatile platform for Cys-peptide–hydrazine conjugation and interplay. Issue 35 (2nd September 2021) - António, João P. M.; Faustino, Hélio; Gois, Pedro M. P.
Abstract : Correction for 'A 2-formylphenylboronic acid (2FPBA)-maleimide crosslinker: a versatile platform for Cys-peptide–hydrazine conjugation and interplay' by João P. M. António et al., Org. Biomol. Chem., 2021, 19, 6221–6226, DOI: ; 10.1039/D1OB00917F .